Impulse Control Disorders with the use of Dopaminergic Agents in Restless Legs Syndrome: a Case-Control Study - Cornelius, Jason R. (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: To determine the frequency of impulse control disorders (ICDs) with the use of dopaminergic agents in restless legs syndrome (RLS). DESIGN: Prospective case-control study using a screening questionnaire for ICDs, followed by phone interview to confirm diagnoses for those meeting preset scoring thresholds on the questionnaire. SETTING: Academic, comprehensive sleep medicine center. PATIENTS OR PARTICIPANTS: (1) One hundred patients with RLS treated with dopaminergic agents, (2) 275 patients with obstructive sleep apnea (OSA) without RLS or exposure to dopaminergic agents; and (3) 52 patients with RLS who were never treated with dopaminergic agents. Subjects with parkinsonism were excluded. INTERVENTIONS: Not applicable. MEASUREMENTS AND RESULTS: Based on the questionnaire, frequencies of ICDs for the RLS treatment group were 10% compulsive shopping, 7% pathologic gambling, 23% compulsive eating, 8% hypersexuality, and 10% punding. These values were statistically significant when compared with control subjects with OSA for compulsive shopping and pathologic gambling. With additional information from the phone interview, adjusted frequencies for the RLS treatment group were 9% compulsive shopping, 5% pathologic gambling, 11% compulsive eating, 3% hypersexuality, 7% punding, and 17% any ICD. These values were statistically significant when compared with those of control subjects with OSA for compulsive shopping, pathologic gambling, punding, and any ICD, as well as for compulsive shopping when compared with control subjects with RLS who were not treated with dopaminergic agents. In the RLS treatment group, a statistically significant dose effect was found for pramipexole in those subjects confirmed to have ICDs by both the questionnaire and phone interview. Mean duration of treatment at ICD onset was 9.5 months. CONCLUSIONS: ICDs are common with the use of dopaminergic agents for treatment of RLS. Given the potentially devastating psychosocial consequences of these behaviors, it is critical to actively screen for ICDs in this population. CITATION: Cornelius JR; Tippmann-Peikert M; Slocumb NL; Frerichs CF; Silber MH. Impulse control disorders with the use of dopaminergic agents in restless legs syndrome: a case-control study. SLEEP 2010;33(1):81-87.